Cosmological gas accretion history onto the stellar discs of Milky Way-like galaxies in the Auriga simulations – (I) Temporal dependency. Issue 1 (26th September 2022) - Iza, Federico G; Scannapieco, Cecilia; Nuza, Sebastián E; Grand, Robert J J; Gómez, Facundo A; Springel, Volker; Pakmor, Rüdiger; Marinacci, Federico
ABSTRACT: We use the 30 simulations of the Auriga Project to estimate the temporal dependency of the inflow, outflow, and net accretion rates onto the discs of Milky Way-like galaxies. The net accretion rates are found to be similar for all galaxies at early times, increasing rapidly up to 10 M_ yr^-1 . After ∼6 Gyr of evolution, however, the net accretion rates are diverse: in most galaxies, these exhibit an exponential-like decay, but some systems instead present increasing or approximately constant levels up to the present time. An exponential fit to the net accretion rates averaged over the MW analogues yields typical decay time-scale of 7.2 Gyr. The analysis of the time-evolution of the inflow and outflow rates, and their relation to the star formation rate (SFR) in the discs, confirms the close connection between these quantities. First, the inflow/outflow ratio stays approximately constant, with typical values of M_out/ M_in 0.75, indicating that the gas mass involved in outflows is of the order of 25 per cent lower compared to that involved in inflows. A similar behaviour is found for the SFR/inflow rate ratio, with typical values between 0.1 and 0.3, and for the outflow rate/SFR, which varies in the range 3.5–5.5. Our results show that continuous inflow is key to the SFR levels in disc galaxies, and that the star formation activity and the subsequent feedback in the discs is able to produce mass-loaded galaxy winds in the disc–halo interface.